A theoretical investigation ofthe resonance damping performance of magnetic material coating in Power/Ground plane structures - Wu, LK; Tseng, CH (My University, 2005)
Power bus structure, consisting of two parallel solid power and ground planes separated by an insulator, behaves as a cavity resonator at high frequencies. Noise on the power bus, due to a sudden change in the current drawn by an active component, can appear as an undesired spatial fluctuation in the voltage between power and ground, especially at resonant frequencies of the resultant cavity, which may lead to problems in signal integrity, excessive delays, false switching, and radiated emission. These resonances can be suppressed by introducing high-frequency loss into the structure. This paper investigates a simple method to reduce self-/transfer impedance of power/ground planes for mitigating power/ground bounce in high-speed printed circuit board design by adding a thin layer of magnetic material coating to the inside-facing surfaces of copper power and ground plates to increase their effective high-frequency surface impedance. The increased surface impedance will increase the attenuation constant of the propagating wave inside the cavity that benefits reduction of cavity's quality factor (Q factor). The simulation results obtained from a modified cavity resonator model show that increasing surface impedance can dramatically reduce self- and transfer impedances at board resonant frequencies.
Keywords: cavity resonator model; ground bounce; magnetic material coating; self-/transfer impedance; simultaneous switching noise (SSN); surface impedance